2017
DOI: 10.1097/mlr.0000000000000685
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Disparities in Mortality Among Women With Incident Breast Cancer Before and After Implementation of Medicare Part D

Abstract: Background Breast cancer patients exhibit survival disparities based on socioeconomic status (SES). Disparities may be attributable to access to expensive oral endocrine agents. Objectives Define recent socioeconomic disparities in breast cancer survival and determine whether these improved after implementation of the Medicare Part D program. Design Difference-in-difference natural experiment of women diagnosed and treated before or after implementation of Medicare Part D. Subjects Female Medicare benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…Much of the existing literature on racial disparities focuses on poorer survival among racial groups once the cancer is diagnosed, with less focus on incidence or prevention (other than tobacco reduction). 18,19 Our findings suggest that cancer incidence, mortality, and survival disparities warrant attention. Cancer November 1, 2019 There are plausible mechanisms by which mortgage discrimination might cause greater cancer incidence or poorer survival among blacks.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Much of the existing literature on racial disparities focuses on poorer survival among racial groups once the cancer is diagnosed, with less focus on incidence or prevention (other than tobacco reduction). 18,19 Our findings suggest that cancer incidence, mortality, and survival disparities warrant attention. Cancer November 1, 2019 There are plausible mechanisms by which mortgage discrimination might cause greater cancer incidence or poorer survival among blacks.…”
Section: Discussionmentioning
confidence: 78%
“…18 The relationship between mortgage discrimination and cancer mortality disparities is attenuated, but not eliminated, when adjusting for incidence disparities, suggesting that both incidence and survival are factors relevant to the relationship between mortgage discrimination and cancer mortality disparities. In MSAs with higher levels of mortgage discrimination, blacks are at a greater cancer mortality disadvantage compared with whites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the disadvantages of low socioeconomic status on outcomes from diverse major medical conditions such as diabetes, 7 asthma, 33 acute myocardial infarction, 34 and breast cancer. 35 These data collectively represent a substantial public health challenge, and future studies are needed to elucidate the mechanisms by which differences in socioeconomic status mediate differences in outcomes, so that targeted interventions can be designed and assessed.…”
Section: A Number At Riskmentioning
confidence: 99%
“…In particular, health disparity populations of Blacks/African Americans, low-income populations, and rural populations tend to have low utilization rates [4][5][6]. Low screening utilization in turn translates into delayed diagnosis and decreased survival rates [7][8][9][10][11]. Curtis et al found that differences in screening behaviors accounted for a considerable portion of mortality differences between populations [12].…”
Section: Introductionmentioning
confidence: 99%